2002
DOI: 10.1042/ba20020010
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative physical characterization of lipid–polycation–DNA lipopolyplexes

Abstract: Quantitative assays for the characterization of multi-component lipopolyplexes and their individual constituents are crucial for determining the consistency of formulation protocols which are ultimately reflected in biological activity. Lipid-polycation-DNA formulations consisting of lipids, polycations and DNA are of interest because they have been demonstrated to be efficient gene-delivery vehicles when administered systemically. We have developed a panel of analytical techniques to characterize these lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The effectiveness of the Pico Green fluorescent probe was also explored by Tsai et al [53], who identified the quenching of the fluorescence signal at increasing complexing protamine/DNA ratios. The fluorescence signal is proportional to the accessibility, that means the availability of DNA to complexation to the probe.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the Pico Green fluorescent probe was also explored by Tsai et al [53], who identified the quenching of the fluorescence signal at increasing complexing protamine/DNA ratios. The fluorescence signal is proportional to the accessibility, that means the availability of DNA to complexation to the probe.…”
Section: Discussionmentioning
confidence: 99%
“…8 In 1997, Huang and coworkers 9 introduced cationic polypeptide protamine into liposome to form lipid-polycation-DNA lipopolyplexes (LPD), which have appeared promising as efficient gene-delivery vehicles for systemic administration. 10 Therefore, according to its constructional mechanism, the combined use of polycationic peptide and biodegradable macromolecular polymer to be a novel multi-polyplex gene delivery system is presented. PLGA microspheres containing PLL-pDNA were formulated by Capan et al 11 and PLGA-grafted PLL (PLL-g-PLGA) micelles were produced by Jeong.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Combinations of cationic liposomes and polymers with DNA have been called lipopolyplexes. 6,7 Molecular conjugates, in this review, will refer to combinations of peptides or proteins with DNA. These vectors may also include combinations of peptides or proteins with either of vectors 1-3 in Table 1.…”
Section: Introductionmentioning
confidence: 99%